Experimental investigation on suitability of Surfactin for enhanced oil recovery: Stability, adsorption equilibrium and kinetics studies. Issue 1 (February 2022) - Datta, Poulami; Tiwari, Pankaj; Pandey, Lalit M.
Abstract: Surfactants have the capability to decrease interfacial tension (IFT) between water and residual oil, which improves the oil recovery factor. But one of the major difficulties in surfactant flooding is the adsorption phenomenon of surfactant onto the solid surfaces, which decrease its effectiveness in lowering the IFT for enhanced oil recovery (EOR) application. This study discusses the adsorption behavior of Surfactin (lipopeptide biosurfactant) onto sandstone silica samples in the diverse temperature range. The stability of the produced biosurfactant was analyzed at extreme environmental conditions. The pretreated adsorbent was characterized and adsorption equilibrium, kinetics and thermodynamic studies were performed. Amongst alternative models, the Freundlich isotherm model and Elovich kinetics fitting better described the characteristics of the Surfactin adsorption. The intraparticle diffusion (IPD) analysis also represented the presence of two distinct steps in the entire process: rapid adsorption and intraparticle diffusion. Thermodynamical spontaneity of the adsorption process has also been investigated to substantiate the feasibility of the entire process. The results provided novel perceptions about real-time surfactant adsorption properties, that are frequently overlooked in conventional methodologies and approaches. Graphical Abstract: ga1 Highlights: Adsorption study of Surfactin (lipopeptide biosurfactant) was performed on sand surface. EDX, XRD and BET analyses were conducted to characterize the pretreated sand. Adsorption isotherms were employed to determine the best-fit equilibrium model. Kinetic and thermodynamic analyses of the Surfactin adsorption were investigated. The stability of Surfactin at extreme temperature, pressure and salinity was accessed.